Effect of Occupational Safety and Health and Incentives on Work Motivation and Employee Performance (Study in Employees of PT. YTL-Paiton Province East Java) - Maharani Ikaningtyas; Mochammad Al Musadieq; Arik Prasetya (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
This research in PT YTL and was conducted to determine the effect of independent variables namely Occupational safety, Occupational Health, and Incentives on the dependent variable namely Employee Performance through the intervening variable namely Work Motivation. This research is a type of explanatory research with a quantitative approach. The data used in this study are primary data obtained from questionnaires. The researcher used probability sampling techniques, namely proportionate random sampling using Slovin formula and obtained a sample of 78 respondents. Data analysis in this study used the Path Analysis method with the help of SPSS. The results of this study indicate that Occupational Safety, Occupational Health, and Incentives are positive and significantly influence the Work Motivation. Variable work motivation is a positive and significant effect on employee performance. Furthermore, Occupational Safety, Occupational Health, and Incentives are positive and significantly influence Employee Performance. Furthermore, there are indirect effects between the variables of Occupational Safety, Occupational Health, and Incentives on Employee Performance through Work Motivation variables.